The copyright handbook : what every writer needs to know - Fishman, Stephen (Nolo, 2021)
No writer or content creator wants to see their work copied. Learn how to protect yourself and your hard work, with the number one handbook on copyright law for writers and anyone who works with words. This all-in-one resource shows you how to register your work, maximize copyright protection (including internationally), understand the'fair use'rule, deal with infringers (online and off), get permission to use copyrighted work, profit from your copyright, and much more.